A Descriptive Study about Factors Affecting Data Quality of EWARS in Surabaya 2016 - Sobhita Paramita (Universitas Airlangga, 2017)
Early Warning Alert and Response System (EWARS) is a health information technology that is used for recording and reporting diseases especially those that have the potential to cause outbreaks and can produce